A Review of the Free Schemes Operated by the Department of Social, Community and Family Affairs - Orlaigh, Quinn (Trinity College Dublin, 2000)
A Review of the Free Schemes Operated by the Department of Social, Community and Family Affairs examines the social welfare benefit-in-kind schemes: Free Travel, Free Electricity/Gas Allowance, Free TV Licence and Free Telephone Rental Allowance. It examines the underlying rationale of the schemes and their performance using efficiency criteria and customer views, and assesses their overall contribution to combating poverty and social exclusion. The research is greatly enhanced by the results of surveys conducted with the recipients of the schemes. Demands to extend the schemes to other groups are examined and a number of recommendations proposed. Payment arrangements with the service providers are analysed in the light of State sector deregulation.
Keywords: Public Policy; Free schemes; Ireland